Non-line-of-sight radar - Watson, Brian C.; Guerci, J. R. (Artech House radar library., 2019)
Bringing together the essential underpinnings and techniques required to develop and field a viable NLOS radar, this book presents many examples, including electromagnetic radiation propagation in urban NLOS environments, predictive ray-tracing techniques, and more. --